TAQWA: SEBAGAI LEARNING OUTCOME PENDIDIKAN AGAMA ISLAM:ANALISIS NORMATIF-HERMENEUTIK TERHADAP HADIST TARBAWI - Asmara Hayati24; Ainun Nisa; Aulia Annisa; Desta Tri Wahyuni; Dwi Suci Sisca Sari (IAIN Ambon, 2026)
Abstract: Islamic Religious Education (IRE) is not merely oriented toward academic achievement but also toward the formation of pious individuals. However, the implementation of learning outcomes in modern education often emphasizes cognitive achievement more than spiritual and moral dimensions. This study aims to analyze the concept of taqwa in educational hadith through a normative-hermeneutic approach and to examine its relevance as a learning outcome of Islamic Religious Education. This research employs a qualitative method with a library research design. Primary data were obtained from educational hadith concerning taqwa, particularly the hadith narrated by Al-Tirmidhi No. 1987, while secondary data were collected from books, journal articles, and other relevant literature. Data were analyzed descriptively through normative analysis of hadith content and hermeneutic analysis to interpret its meaning and educational relevance. The findings reveal that taqwa encompasses three main dimensions: *tarbiyah imaniyah* (faith development), *tarbiyah nafsiyah* (self-development), and *tarbiyah ijtima'iyah* (social and moral education). These dimensions indicate that taqwa is not limited to spiritual obedience but also includes character formation, self-regulation, and social ethics. Furthermore, taqwa aligns with the concept of learning outcomes as it integrates cognitive, affective, and psychomotor domains. Therefore, taqwa can be positioned as a holistic learning outcome in Islamic Religious Education.